2018
DOI: 10.3390/app8112127
|View full text |Cite
|
Sign up to set email alerts
|

A G3-Continuous Extend Procedure for Path Planning of Mobile Robots with Limited Motion Curvature and State Constraints

Abstract: Provably correct and computationally efficient path planning in the presence of various constraints is essential for autonomous driving and agile maneuvering of mobile robots. In this paper, we consider the planning of G 3-continuous planar paths with continuous and limited curvature in a motion environment that is bounded and contains obstacles modeled by a set of (non-convex) polygons. In practice, the curvature constraints often arise from mechanical limitations for the robot, such as limited steering a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Xue [32] presented a multi-objective evolutionary algorithm for the path planning problem. Another approach, authored by Gawron and Michałek [33], is available for the path planning problem of mobile robots. They showed that their path planning, which is collision-free, satisfies curvature constraints, and preserves continuity of the curvature arc-length derivative.…”
Section: Advanced Mobile Roboticsmentioning
confidence: 99%
“…Xue [32] presented a multi-objective evolutionary algorithm for the path planning problem. Another approach, authored by Gawron and Michałek [33], is available for the path planning problem of mobile robots. They showed that their path planning, which is collision-free, satisfies curvature constraints, and preserves continuity of the curvature arc-length derivative.…”
Section: Advanced Mobile Roboticsmentioning
confidence: 99%
“…According to the principle of geometry, the operating system regards the mobile robot as a point and realizes the path planning of the mobile robot from the start point to the target point [9]. The most direct method is visibility-based graphs, connect the vertices of obstacles to construct different polygons [10][11][12], and then use path planning algorithms to plan the path. The Dijkstra algorithm is a typical method and realizes the shortest path search by accumulating the path length.…”
Section: Introductionmentioning
confidence: 99%
“…The mathematical optimization approaches, firstly formulating a cost function of the automatic parking problem and then minimizing the objective cost function [9][10][11][12][13]. Besides car-like vehicles, reference trajectory is feasible in the case of parking N-trailer vehicles when complicated kinematic constraints are taken into account in planning the trajectory [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…in the case of parking N-trailer vehicles when complicated kinematic constraints are taken into account in planning the trajectory [14][15][16].…”
Section: Introductionmentioning
confidence: 99%